2020
DOI: 10.33271/nvngu/2021-5/100
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the operation efficiency criteria for geothermal probes in flooded mine workings

Abstract: Purpose. To develop and test the energy and cost criteria for evaluating the operation efficiency of a closed geothermal system using coaxial or U-shaped probes that can be installed in flooded workings of mines. Methodology. To justify the energy and cost criteria, we applied thermodynamic, hydraulic and cost-efficiency relationships, conducted the engineering analysis of closed geothermal systems, studied hydrogeological settings and geothermal conditions of the mines of the Selidovo group in Donbas. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Studies, described by paper [32], showed how changes in the geomechanical situation of the rock mass influence its state. It was identified that the major rock mass changes take place at a distance from the mine working periphery of up to five times its radii.…”
Section: Introductionmentioning
confidence: 99%
“…Studies, described by paper [32], showed how changes in the geomechanical situation of the rock mass influence its state. It was identified that the major rock mass changes take place at a distance from the mine working periphery of up to five times its radii.…”
Section: Introductionmentioning
confidence: 99%